Uji Efektivitas Ekstrak Beberapa Jenis Rimpang Jahe (Zingiber officinale Rosc.) Terhadap Patogen Phytophthora palmivora Butl. Penyebab Busuk Buah Kakao - SITEPU, MARTINA E; SUNITI, NI WAYAN; SINGARSA, I DEWA PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Effectiveness of Some Ginger Extracts ( Zingiber officinale Rosc . ) against the Pathogen of Phytophthora palmivora Butl. Causes of Cocoa Fruit Rot   The purpose of this study was to determine the effectiveness of some ginger ( Zingiber officinale Rosc.) extracts to prevent pathogen of Phytophthora palmivora Butl. causes of cocoa fruit rot. In vitro, the concentrations of 0,1%, 0,2%, 0.25%, 0.5%, 1%, 1.5%, 2%, and 2.5% were tested to determine the Minimum Inhibitory Concentration (MIC) while the extract concentration of 0.25%, 0.5%, 1%, 1.5%, 2%, 2.5% were tested to determine the percentage of inhibitability of Phytophtora palmivora Butl. The concentrations of  0.25%, 0.5%, 1%, 1.5%, 2%, and 2.5% were tested in vivo at the Laboratory to determine the effectiveness of extracting ginger rhizomes in controlling fruit rot in cocoa plants. The results of the in vitro test showed that the MIC of Z. officinale var . officinale rhizome extract was 0,25%, while the MIC of Z. officinale var. rubrum rhizome and Z. officinale var. amarum were 0.1%. The concentration of inhibition of Z.officinale var officinal e extract, Z.officinale var rubrum extract and Z.officinale var  amarum extract are most effective against the growth of colonies of Phytopthora palmivora Butl. was 2.5% with the inhibition were 48,74%, 72,78%, 79,03%. The result of the in vivo test showed that the Z.officinale var  amaru m extract  effectively suppressing the attack of cocoa rot fruit pathogens marked by the decrease of  percentage by 80%.